2021
DOI: 10.1101/2021.07.27.453820
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development of an ASO therapy for Angelman syndrome by targeting an evolutionarily conserved region at the start of theUBE3A-AStranscript

Abstract: Angelman syndrome is a devastating neurogenetic disorder for which there is currently no effective treatment. It is caused by mutations or epimutations affecting the expression or function of the maternally inherited allele of the ubiquitin-protein ligase E3A (UBE3A) gene. The paternal UBE3A allele is imprinted in neurons of the central nervous system (CNS) by the UBE3A antisense (UBE3A-AS) transcript, which represents the distal end of the SNHG14 transcription unit. Reactivating the expression of the paternal… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…While the gene�c perturba�ons contribu�ng to AS and PWS have been known for many years, the effect those anomalies have on the chromosome 15q locus and the genome as a whole remains unclear. Mouse models have provided key understandings about the facets of gene regula�ons conserved between the two species, but disease features such as the neuron-specific regula�on of UBE3A imprinted expression and protein targets of UBE3A appear to be unique to humans (Cavaillé et al, 2000;Dindot et al, 2023;Landers et al, 2004;Yamasaki et al, 2003). Available iPSC models have been powerful tools to study these disorders as well.…”
Section: Discussionmentioning
confidence: 99%
“…While the gene�c perturba�ons contribu�ng to AS and PWS have been known for many years, the effect those anomalies have on the chromosome 15q locus and the genome as a whole remains unclear. Mouse models have provided key understandings about the facets of gene regula�ons conserved between the two species, but disease features such as the neuron-specific regula�on of UBE3A imprinted expression and protein targets of UBE3A appear to be unique to humans (Cavaillé et al, 2000;Dindot et al, 2023;Landers et al, 2004;Yamasaki et al, 2003). Available iPSC models have been powerful tools to study these disorders as well.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, human specific ASOs revert functional and molecular changes in patient neurons ( 9 , 15 ). In a recent study, human/cynomolgus monkey cross reactive ASOs targeting the UBE3A-ATS revealed moderate knock-down of the UBE3A-ATS but failed to upregulate UBE3A mRNA and protein levels in non-AS neurons and NHP brains ( 30 ). It was hypothesized to be due to potential feedback regulatory mechanisms that hinder upregulation of UBE3A mRNA and protein in a non-disease context ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, human/cynomolgus monkey cross reactive ASOs targeting the UBE3A-ATS revealed moderate knock-down of the UBE3A-ATS but failed to upregulate UBE3A mRNA and protein levels in non-AS neurons and NHP brains ( 30 ). It was hypothesized to be due to potential feedback regulatory mechanisms that hinder upregulation of UBE3A mRNA and protein in a non-disease context ( 30 ). Here, by generating data across three different species, specifically human derived neurons, NHPs and mice, we provide substantial evidence that potent knock-down of UBE3A-ATS enables unsilencing of paternal UBE3A expression with maximal UBE3A protein upregulation even in a “healthy context”, with no evidence for maternal allele compensation.…”
Section: Discussionmentioning
confidence: 99%
“…This structure consists of a central DNA gap region flanked by two RNA-based wings, which improves target binding capacity and reduces off-target effects. 45 Currently, three RNase H1-dependent ASO drugs are used in clinics to treat various diseases, including Fomivirsen for treating CMV retinitis in patients with AIDS, Mipomersen (Kynamro) for treating familial hypercholesterolemia (FH), and Inotersen (Tegsedi) for treating hereditary transthyretinmediated amyloidosis (hATTR).…”
Section: Molecular Mechanisms and Clinical Research Progress Of Rnasmentioning
confidence: 99%